Reframing Educational Conflict Through Quranic Ethics: A Conceptual Framework for Learning in the Society 5.0 Era - Alif Hibatullah; Abu Bakar; Masruhan Masruhan; Tegar Aulia; Ruqoyyah Amilia Andania (Ulul Albab: Jurnal Studi Islam, 2026)
The development of digital technology in the Society 5.0 era has driven significant transformation in the education system, particularly through the integration of artificial intelligence, big data, and digital learning platforms. Although these innovations improve access to knowledge and learning efficiency, the existing educational literature still tends to emphasize technological aspects without adequately addressing the dynamics of epistemic conflict that emerge from the plurality of knowledge sources within learning environments. This study aims to formulate a conceptual framework for educational conflict management based on Quranic ethical values in order to strengthen pedagogical resilience within the educational ecosystem of Society 5.0. This research employs a qualitative approach using thematic interpretation analysis of several Indonesian Quranic commentaries, including Tafsir Al-Misbah, Tafsir Al-Azhar, and other Indonesian tafsir works, focusing on Quranic narratives that represent the dynamics of knowledge conflict and pedagogical relationships, such as the stories of Prophet Moses and Prophet Khidr, Prophet Moses and the Bani Israil, Prophet Adam and Iblis, and Prophet Ibrahim and his people. The analytical process was conducted through thematic coding of various tafsir sources to identify ethical values relevant to conflict management in education. The findings show that conflicts in the learning process can be managed through Quranic principles such as epistemic patience, intellectual humility, disciplined dialogue, information verification, and moral courage in rational argumentation. These principles are then translated into an operational framework for educational conflict management that includes preventing conflict escalation, managing pedagogical dialogue, and restoring academic relationships. The scientific contribution of this study lies in the development of an educational conflict management framework that integrates thematic Quranic interpretation with the concept of pedagogical resilience in the Society 5.0 context. In this way, Quranic values are understood not only as moral ethics but also as epistemological mechanisms for managing educational conflicts within modern learning environments.